Permasalahan Kelembagaan Pemanfaatan Waduk Darma untuk Kegiatan Budidaya Keramba Jaring Apung di Kabupaten Kuningan Jawa Barat - Amelia Indah Hermawaty (Department of Urban and Regional Planning, Diponegoro University, 2015)
Darma Reservoir is one of water resources in Kuningan which is potentially used to fulfill clean water needs. The increase in fishing activities of Keramba Jaring Apung (KJA) has an impact on the environmental quality around the Darma Reservoir. The study aims to analyze the institutional problems of Darma Reservoir which is used for fishing activities in Kuningan District, West Java. A qualitative approach is used in this study supported by interviews with the national and local governments and farmers of KJA. The results indicate that the institutions of Darma Reservoir utilization are poor and lack of policies, roles and responsibilities, and stakeholder coordination. From the aspect of the policy, there are some problems, such as an overlapping regulations between the central and local governments, no licensing procedures for KJA activities, and lack of socialization regarding the policies and rules of the use of keramba to the community or the relevant institutions. From the aspect of the role and responsibilities, there is an authority change from the local governments to the central government, lack of human resources to manage Darma Reservoir, and less coordination in KJA activities. From the aspect of coordination, there is no direct coordination between the agencies involved in the use of reservoirs, the Coordination Team of Water Resources Management (TKPSDA) as the coordination forum has a lack of function and the missing link between the central government (BBWS) and local governments. The findings suggest that the government as the authority should make an institutional concept with integrated relationship model of an administrative system in order to create a harmonious relationship between the central government and local government in the fisheries activities context.